2020
DOI: 10.1002/advs.202000412
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Specific Biomaterial Accumulation in Human Peri‐Implant Bone and Bone Marrow

Abstract: Metallic implants are frequently used in medicine to support and replace degenerated tissues. Implant loosening due to particle exposure remains a major cause for revision arthroplasty. The exact role of metal debris in sterile peri-implant inflammation is controversial, as it remains unclear whether and how metals chemically alter and potentially accumulate behind an insulating peri-implant membrane, in the adjacent bone and bone marrow (BM). An intensively focused and bright synchrotron X-ray beam allows for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 79 publications
(80 reference statements)
2
41
0
Order By: Relevance
“…A vascularized human bone marrow-on-a-chip that supports differentiation and maturation of multiple blood cell lineages also recapitulates myelo-erythroid toxicities after clinically relevant exposures to chemotherapeutic drugs and ionizing radiation, as well as bone marrow recovery after drug-induced myelosuppression (10). Moreover, an MPS model composed of bone tissue was exposed to hip implant-associated dissolved cobalt and chromium at clinically relevant concentrations, which led to the identification of direct cytotoxic effects and successfully verified the integration of chromium into cancellous bone and binding to intertrabecular matrix previously found in patients (11).…”
Section: Human Microphysiological Systems For Drug Developmentsupporting
confidence: 54%
“…A vascularized human bone marrow-on-a-chip that supports differentiation and maturation of multiple blood cell lineages also recapitulates myelo-erythroid toxicities after clinically relevant exposures to chemotherapeutic drugs and ionizing radiation, as well as bone marrow recovery after drug-induced myelosuppression (10). Moreover, an MPS model composed of bone tissue was exposed to hip implant-associated dissolved cobalt and chromium at clinically relevant concentrations, which led to the identification of direct cytotoxic effects and successfully verified the integration of chromium into cancellous bone and binding to intertrabecular matrix previously found in patients (11).…”
Section: Human Microphysiological Systems For Drug Developmentsupporting
confidence: 54%
“…Nonresorbable fixation systems made of titanium (Ti) are the most widely used applications for this purpose, due to their good mechanical properties and biocompatibility, but are also associated with typical disadvantages, similar to delayed osteointegration and microbial colonization [56,57]. An additional concern is the reported accumulation of material particles around Ti and ceramic implants [58,59] However, the main disadvantage for nonresorbable fixation screws is the requirement for their subsequent surgical removal and the resulting risks for the patient [9,49,56,57,60]. Bioresorbable screws, made from polymers such as polylactide and polyglycolide and their copolymers are also available [22,23,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Al can be transported around the body via the bloodstream, bound to transferrin [ 64 ], leading to toxic effects including malignancies [ 65 ], or playing a role in central nervous system degenerative diseases [ 66 ]. Due to its intrinsic proximity to the bone tissue, Al could also accumulate in the bones as it was recently found that metal-specific biomaterials can be accumulated in the peri-implant bone tissue [ 67 ]. The accumulation of Al in bone has also been related to bone fractures accompanying specific diseases [ 68 ].…”
Section: Resultsmentioning
confidence: 99%